Thermal management of three identical PV-TEG units by using different vortex promoters and corner porous partition in a Z-shaped nano-enriched cooling channel and performance estimation using autoencoder - Selimefendigil, Fatih; Kocyigit, Yucel; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
Photovoltaic (PV) panels require effective cooling strategies for performance improvement. In the present study, Z shaped nano-enriched cooling channel is used with different shaped vortex promoters (VPs) along with a porous corner partition for thermal management of three identical PV units combined with thermoelectric generator (TEG) modules. PV-TEG units are mounted on the different parts of the Z-channel (A unit-lower horizontal channel, B unit-vertical channel and C unit-upper horizontal channel) while porous partition used in the corner of the lower horizontal and vertical channel. Three dimensional numerical studies are conducted by using finite element method (FEM) for various values of channel flow Reynolds number (between 100 and 500), various VP shapes (I, L, T and L2-shaped) and nanoparticle loading in water (between 0 and 0.03). Combined use of porous partitions and VPs are influential in the flow field variation and cooling performance improvement in the Z-shaped channel. When compared to reference scenario of using no-VP and no partition at Re=100, using L2-shaped VP at Re=500 results in PV-cell temperature reduction of 8.8 degrees C and 12.9 degrees C for units A and C. When metal foam (MF) is mounted, the average cell temperature for unit B decreases by 4.1 degrees C at Re=100 and 2 degrees C at Re=500 compared to the scenario without VPs. The average cell temperature for unit B drops by 4.1 degrees C at Re=100 and 2 degrees C at Re=500 when porous partition is mounted in comparison to the case without VPs in the cooling channel. Using nanofluid (NF) leads to improved cooling performance in each sub-channels of the Z-shaped cooling system. When porous partition and L2-shaped VP are used in the cooling channel, employing NF at the maximum loading reduces the PV-cell temperature of A, B, and C PV units by 1.2 degrees C, 2 degrees C, and 2.3 degrees C compared to the case of utilizing only water. When corner partition is employed, the PV-cell temperature reductions between the best and worst cases of units A, B, and C are 10.1 degrees C, 12.1 degrees C, and 17 degrees C. The triple PV-TEG unit combined system performance with cooling channel is estimated using an autoencoder-based technique.
Keywords: PV cooling; Nano-enriched Z-shaped channel; Vortex promoters; Porous media; multiple PV-TEG units; Computational fluid dynamics; Autoencoder